Context aware medium access control for buffer-aided multichannel cognitive networks - Darabi, Mostafa; Maham, Behrouz; Saad, Walid; Mehbodniya, Abolfazl; Adachi, Fumiyuki (Institute of Electrical and Electronics Engineers Inc., 2016)
In this paper, a novel context aware medium access control (MAC) scheme is proposed for multichannel buffer-aided cognitive networks. The proposed scheme allows management of the delay of the primary network (PN) and secondary network (SN) more efficiently by exploiting the packets' context. In the proposed multiple access policy, two different context aware approaches for packet prioritization are presented.
Keywords: Average waiting time of packet; Context aware cognitive networks; Little law; Priority-based MAC scheme; Research Subject Categories::TECHNOLOGY::Engineering physics